Synthesis and Characterization of Graphene Oxide and Reduced Graphene Oxide Composites with Inorganic Nanoparticles for Biomedical Applications - Jagiełło, Joanna (Nanomaterials (Basel), 2020)
Graphene oxide (GO) and reduced graphene oxide (RGO), due to their large active surface areas, can serve as a platform for biological molecule adhesion (both organic and inorganic). In this work we described methods of preparing composites consisting of GO and RGO and inorganic nanoparticles of specified biological properties: nanoAg, nanoAu, nanoTiO(2) and nanoAg(2)O. The idea of this work was to introduce effective methods of production of these composites that could be used for future biomedical applications such as antibiotics, tissue regeneration, anticancer therapy, or bioimaging. In order to characterize the pristine graphene materials and resulting composites, we used spectroscopic techniques: XPS and Raman, microscopic techniques: SEM with and AFM, followed by X-Ray diffraction. We obtained volumetric composites of flake graphene and Ag, Au, Ag(2)O, and TiO(2) nanoparticles; moreover, Ag nanoparticles were obtained using three different approaches.